Managerial problems associated with the interventions for teenage pregnancy in the Kumasi Metropolis - Agyemang, Nelson Godfried (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirement for the award of Master of Science Degree in Health Services Planning and Management